Kesalehan atau Kebenaran: Analisis Terjemahan כָּל־צִדְקֹתֵ֑ינוּ (kol-ṣiḏqōtếnû) dalam Yesaya 64:6 - Simbolon, Andreas Kongres Pardingotan; Christian, Ade Widi; Ziliwu, Alnodus Jamsenjos Indirwan (Angelion: Jurnal Teologi dan Pendidikan Kristen, 2023)
Isaiah 64:6, which states that "all our righteousness" is like filthy rags, has been the subject of debate and discussion in Christian theology. This journal aims to explore the concept of righteousness as a condition for human salvation in interpreting this verse. The journal begins by conducting an in-depth analysis of Isaiah 64:6, highlighting keywords such as "filthy rags, menstruation, righteousness, or piety," as well as the textual context within prophetic writings. In this analysis, I argue that human righteousness plays a crucial role in salvation. I describe how righteousness, as a manifestation of humility and repentance, can be the first step in seeking the grace of God and faith in Jesus Christ. Over time, this journal elaborates on how righteousness can become a determining factor in the relationship between humans and God. The goal of this journal is to convey the idea that human righteousness can be a prerequisite that leads people into the embrace of God's grace. It is an effort to delve into the meaning and role of righteousness in Christian theology and to provide a perspective that supports the notion that righteousness is a key factor in the journey toward salvation.